1970
DOI: 10.1063/1.1659030
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and Structure of GdN and GdN1−xOx

Abstract: GdN is shown to be ferromagnetic but small amounts of oxygen (GdN1−xOx with x≈0.05) cause paramagnetism and short-range antiferromagnetic order to set in. We attribute this to nearest-neighbor interactions having opposite sign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0
1

Year Published

1972
1972
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 4 publications
5
35
0
1
Order By: Relevance
“…The lattice parameter of the NaCl face-centered-cubic structure was derived to be 4.83670.005Å, comparable to the literature bulk data of 4.83Å. As oxygen inclusions in RN have been demonstrated to decrease the lattice parameter [21,22], we believe that the ErN film is highly stoichiometric and that potential residual oxygen is confined at the interface.…”
Section: Film Preparation and Characterizationmentioning
confidence: 64%
“…The lattice parameter of the NaCl face-centered-cubic structure was derived to be 4.83670.005Å, comparable to the literature bulk data of 4.83Å. As oxygen inclusions in RN have been demonstrated to decrease the lattice parameter [21,22], we believe that the ErN film is highly stoichiometric and that potential residual oxygen is confined at the interface.…”
Section: Film Preparation and Characterizationmentioning
confidence: 64%
“…The authors note the similarity of the behavior to that of EuO. 23 However, unlike EuO, the exchange mechanism that gives rise to the magnetic behavior in GdN is not yet clear, 3,5,7,8,24,25 and the role of charge carriers in mediating the exchange is not understood.…”
Section: Introductionmentioning
confidence: 91%
“…The most thoroughly studied of these is GdN, and although early studies produced conflicting results regarding the magnetic ordering, 3,4 GdN is now generally accepted to be ferromagnetic below about 70 K with a saturation moment of ϳ7 B / Gd. [5][6][7][8][9][10][11] More recently, advanced band structure calculations that take into account the magnetic order have predicted a range of electronic structures in the ferromagnetic ground state of GdN. Aerts et al, 12 using density functional theory in the local-spin-density approximation with a self-interaction correction, found that exchange splitting of the predominantly Gd s-d-like and N p-like conduction band states is sufficient to cause GdN to be halfmetallic, meaning that there are mobile electrons at the Fermi level of one spin only.…”
Section: Introductionmentioning
confidence: 99%
“…Gadolinium nitride films can convert to oxide when exposed to air at ambient temperature within a few tens of second [15]. Furthermore, oxygen contamination will largely inhibit the ferromagnetic properties of gadolinium nitride [16,17], therefore it is of utmost importance to grow films with high purity and to avoid post-growth oxidation. Gadolinium nitride has previously been deposited by MolecularBeam Epitaxy (MBE) [15,18], Physical Vapor Deposition (PVD) [19,20], Pulsed Laser Deposition (PLD) [10] and very recently, Chemical Vapor Deposition (CVD) [21,22].…”
Section: Introductionmentioning
confidence: 99%